(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The need to comprehensively use the whole system of generalizing and individual indicators in the assessment of management efficiency in oil enterprises arises from the complexity of assessing the efficiency of the management process. Because, the effectiveness of management activities in relation to the subject of management can be characterized by quantitative and qualitative indicators